Laparoscopic hyperthermic intraperitoneal chemotherapy for appendiceal tumors. Issue 4 (29th January 2020) - Sommariva, Antonio; Tonello, Marco; De Simoni, Ottavia; Barina, Andrea; Riccardo Rossi, Carlo; Pilati, Pierluigi
Abstract: Introduction: The application of hyperthermic intraperitoneal chemotherapy (HIPEC) in colorectal and appendix cancer at risk of peritoneal seeding is an appealing strategy to prevent peritoneal metastases. Here, we present the technical details and postoperative outcomes of laparoscopic HIPEC performed with prophylactic intent in three patients with low‐grade appendiceal neoplasm (LAMN) considered at risk of peritoneal recurrence. Materials and Surgical Technique: Three patients with LAMN previously treated outside our department were selected for second‐look laparoscopic exploration and HIPEC. The study received institutional review board approval. A Hasson trocar was inserted around the umbilicus. Four additional 10‐mm trocars were inserted—one each in the left and right upper and lower quadrants. After full abdominal exploration, laparoscopic cytoreductive surgery was performed. Perfusion catheters were inserted through the four lateral trocars in the abdominal quadrants. HIPEC was performed with mitomycin 12 mg/m 2 and cisplatin 90 mg/m 2 for 60 minutes at a target temperature of 41.0°C. The postoperative course was uneventful, except for an episode of fluid leak due to dural tear (treated with supine bed rest for 48 hours and resulting in no adverse sequelae). The median length of hospital stay was 11 days. After a median follow‐up of 36 months, all patients were asymptomatic with no evidence of recurrence. Discussion: Laparoscopic HIPEC for LAMN at risk of peritoneal recurrence appeared to be feasible, safe, and associated with a favorable postoperative outcome. More studies with larger samples of patients and with a standardized design are needed to better analyze the oncological value of this approach.